Functional genomics of NAC transcription factor SND2 regulating secondary cell wall biosynthesis in Arabidopsis and Eucalyptus - Myburg, Alexander Andrew (University of Pretoria, 2021)
Thesis (PhD)--University of Pretoria, 2014.